2004
DOI: 10.1152/ajpheart.00085.2004
|View full text |Cite
|
Sign up to set email alerts
|

Electrical current-induced atrial and pulmonary vein action potential duration shortening and repetitive activity

Abstract: The influence of threshold electrical currents (EC) during regular drive on pulmonary vein (PV) and atrial myocardial cell action potential (AP) duration (APD) is unknown. We determined the effects of EC on cellular APD of PV, atria, and ventricles in isolated perfused and superfused male rat hearts (Fisher-344 strain, 3-4 mo old) at 37 degrees C (n = 14). We determined APD changes caused by subthreshold and threshold EC synchronized with a distant pacing electrode and delivered nearby cells from which transme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…ACh activates I K(ACh) and thereby decreases the refractory period and hyperpolarizes the cell membrane (25). Such effects accelerate reentrant rotors maintaining AF and increase their angular velocity (30).…”
Section: Interactions Among Ach Concentrations/distributions and Tissmentioning
confidence: 99%
“…ACh activates I K(ACh) and thereby decreases the refractory period and hyperpolarizes the cell membrane (25). Such effects accelerate reentrant rotors maintaining AF and increase their angular velocity (30).…”
Section: Interactions Among Ach Concentrations/distributions and Tissmentioning
confidence: 99%
“…Despite many investigations, the mechanism generating focal activity in the pulmonary veins remains unknown (see Nattel, 2002 ; Page and Roden, 2005 for reviews). Most studies have concentrated upon pathological alterations to the electrophysiology of cardiac muscle cells in the pulmonary vein, including the possibility of delays in action potential conduction ( Chen et al ., 2000 ; Verheule et al ., 2002 ), alterations of action potential duration and effective refractory period ( Chen et al ., 2001 ; Jalife et al ., 2002 ; Scherlag et al ., 2002 ), high‐frequency firing and cellular Ca 2+ overload causing early after depolarizations ( Schauerte et al ., 2001 ; Miyauchi et al ., 2004 ; Patterson et al ., 2005 ), alterations in ion channels that might cause abnormal automaticity ( Bosch and Nattel, 2002 ; Khan, 2004 ; Melnyk et al ., 2005 ), and finally, automatism resulting from the activity of nodal myocytes in the pulmonary vein ( Masani, 1986 ; Chen and Yeh, 2003 ; Perez‐Lugones et al ., 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (5)(6)(7)(8) found myocytes exhibiting automaticity in PV sleeves, with action potentials (APs) resembling those found in the sinoatrial node, but several other groups failed to find such automaticity under physiological conditions in tissue preparations (1,9,15,16,22,38). Reentry, the second mechanism, has been observed to occur in normal canine PVs (1) and apparently in PVs of patients with AF (20).…”
mentioning
confidence: 99%